Diabetes and Pancreatic Cancer - De Souza, Andre Luiz; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Context Pancreatic cancer is the fourth leading cause of cancer mortality in the United States. Most of the patients are diagnosed in the metastatic staging. Consolidated risk factors include chronic pancreatitis, smoking and family history. Although controversial, diabetes mellitus has been increasingly associated with pancreatic cancer as a risk factor as opposed to just a manifestation of the disease. Biomarkers for early diagnosis of pancreatic cancer among diabetic patients and metformin as a biologic therapy for pancreatic cancer are herein discussed. Methods Review of the literature and evaluation of two Abstracts (#180 and #253) from the 2014 ASCO Gastrointestinal Cancers Symposium focusing on pancreatic adenocarcinoma and diabetes diagnosis and therapeutics. Results Abstract #180 discusses the role of metabolic biomarkers in the early diagnosis of pancreatic cancer among diabetic patients, especially recently diagnosed. Abstract #253 debates metformin as a candidate radiosensitizer for pancreatic cancer, although it fails to reject its null hypothesis. Conclusion Search for methods that can identify pancreatic cancer patients among new-onset diabetic patients could result in early diagnosis of this lethal disease. Metformin is a target therapy that increases median overall survival but is not a radiation sensitizer in patients with pancreatic cancer who present with diabetes. Image: Metformin effect in cellular pathways involved in pancreatic cancer (Figure 1)